Islamic Monetary Policy and Rastin Swap Bonds - Bidabad, Bijan (International Journal of Islamic Banking and Finance Research, 2019)
Purpose: This paper aims to examine monetary instruments in Islamic central banking framework. As a conclusion, to revive Islamic monetary policy, we should provide some public equity-based instrument as a necessary replacement for conventional bonds and treasury bills to activate non-usury open market operations.Design: We define a type of new negotiable bond as: “Rastin Swap Bonds (RSBs)”, which is based on swapping money between two persons for two different periods.Findings: RSB is a financial paper that observes the right for the lender to borrow an equal amount to his lending from the borrower. Four types of RSBs in domestic money and foreign currency are defined, and their Sharia allowances and monetary, fiscal, and financial effects are evaluated.Research limitations: This bond is a novel design, and it is required to be more elaborated for further practical development and adjustment.Practical implications: Islamic central banking is not different from conventional central banking as a whole, but the role of an Islamic central bank in conducting monetary policy is restricted to use interest-free monetary instruments in an environment that commercial banks are obliged to implement non-usury banking operations.Social implications: Islamic financial instruments should be usury-free and efficient in applying monetary, fiscal, and financial policies at different levels of the central bank, government and commercial banks and non-banking money and financial institutions. Rastin Swap Bond will serve as an important instrument for resource mobilization and will be a primary vehicle for the development of the Islamic capital market and central banking operations.Originality/value: Conventional interest-bearing bonds are not allowed in Islamic central banking. This restriction mostly distinguishes Islamic central banking from the conventional one in implementing monetary policy.Article Type: Technical paperJEL: G21, G28, H81